Gender and Science in Development: Women Scientists in Ghana, Kenya, and India - Patricia Campion and Wesley Shrum (Science Technology Human Values 2004; 29; 459, 2004)
Why do women have more difficulty pursuing research careers than men? Although this topic has been extensively investigated in industrialized countries, prior studies provide little comparative evidence from less-developed areas. Based on a survey of 293 scientists in Ghana,Kenya, and the Indian state of Kerala, this article examines gender differences on a variety of individual, social, and organizational dimensions. The results show small or nonexistent differences between women and men in individual characteristics, professional resources, and the organizational conditions under which research is conducted. The article argues that a combination of educational and research localism increases the likelihood of restricted professional networks for women. Gender inequality in the research systems of the developing world may be based on systemic deficits in the acquisition of social rather than material resources. The most important implication is that educational policy for development should focus on international opportunities for women in the near future.